AN ANALYSIS OF DESIGN FLOOD DISCHARGE IN PARANGJOHO WATERSHED USING THE METHODS OF SYNTHETIC UNIT HYDROGRAPH (SUH) AND SOIL CONVERSATION SERVICE (SCS) - ridwan abadi akbar; Adwitya Bhaskara (Reviews in Civil Engineering, 2020)
Abstract.Floods always come suddenly and unexpectedly, and lots of people living in the flood-prone area can be the victims. As happened on February 2, 2020, a number of rice fields, roads, and houses belonging to the residents in the Parangjoho watershed, Eromoko District, Wonogiri, with 9.8-km river length and 32.59-km2 area, was flooded due to heavy rain for some time which flushed the Eromoko area, therefore, the river flow could not accommodate the volume of water that entered and overflowed. This was what motivated researchers to calculate the design flood discharge to be able to carry out the flood control.The methods of calculating the design flood discharge in the Parangjoho watershed used the Nakayasu Synthetic Unit Hydrograph (SUH) Method and the Soil Conservation Service (SCS) Method, using the rainfall data from the Bengawan Solo Central River Region at Parangjoho Station. The rainfall data used were from 2000 to 2019.